BURN INJURY: GENERAL CONCEPTS AND INVESTIGATION BASED ON ANTEMORTEM AND POSTMORTEM OF CLINICAL INJURY - Sintia Dewi, Yulia Ratna (E-Jurnal Medika Udayana; vol 2 no 7 (2013):e-jurnal medika udayana, 2013)
Burn injury is a condition which catastrophic consequences can affect the sufferer physically, socially, as well as financially. Medicolegal aspect of a burn requires physicians to be able to examine burn injuries on both the living and the dead. Burn injury is defined as tissue damage due to contact with dry heat (fire), humid heat (vapor or hot liquid), chemicals (corrosive agents), electrical devices (lamp or electrical current), friction, as well as electromagnetic energy. Burn can be classified according to its breadth and degree. Death by burn injuries can be classified into 2 categories which are slow death and the fast one. The difference between antemortem and postmortem burn injury is that antemortem injury will show several intravital signs in the bullae and vesicles while postmortem injury will have none.Three main points exist in identifying antemortem and postmortem burn injuries, namely redness lines, vesication, and reparative processes. Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: burn injury, general concepts, antemortem, postmortem